Factor that influenced the acceptance of the internet banking among workers case study in Schlumberger Financial Hub Kuala Lumpur / Mohamad Solehin Ismail and Nur Farhanah Abu Bakar Sided - Ismail, Mohamad Solehin; Abu Bakar Sided, Nur Farhanah (Faculty of Business and Management, 2014)
This study is focus on factor that influences the acceptance of internet banking among workers: Study in the Schlumberger Financial Hub Kuala Lumpur. The research is focusing on the group in the Schlumberger Financial Hub Kuala Lumpur. The objective of this study is to determine factors that influence the acceptance of internet banking among workers. The theoretical framework of this study consists of dependent variable and independent variables. The sample size of this study was 150 0f employees in the Schlumberger Financial Hub Kuala Lumpur. Data was obtained using primary and secondary data. Respondent were required to answer the questionnaires that statement of each variable. Once the necessary data was collected, the data was analyzed and summarized in reliability and easily interpret form. The Statistical Package for the Social Science (SPSS) version 20 was used to summarize the data. The results are in form of reliability testing, frequency distribution, pearson’s correlation coefficients and regression analysis. Based on this research, all independent variable which are perceived ease of used, perceived risk and perceived usefulness have a positive significant with the acceptance of internet baking among workers. Even though, perceived ease of used is the most influence the acceptance of internet banking among workers. Based on the literature review, some recommendation has been suggested in order to improve the banks and related problem occur.